Unbreakable [videorecording (Blu-Ray) ] - Shyamalan, M. Night; Willis, Bruce, 1955-; Jackson, Samuel L.; Wright, Robin, 1966-; Woodard, Charlayne (Distributed by Buena Vista Home Entertainment, 2008)
David Dunn is the sole survivor of an horrific train crash that killed 131. Everyone, especially David, is wondering how it could be possible. Soon, David is approached by comic book specialist Elijah Prince, who confronts David with an incredible theory that just might explain the situation.